Food insecurity among older Europeans: Evidence from the Survey of Health, Ageing, and Retirement in Europe - Peng Nie; Alfonso Sousa-Poza (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2016)
Using data from the fifth wave of the Survey of Health, Ageing and Retirement in Europe, this study investigates the association between food insecurity (FI) and several demographic, socioeconomic, and health-related characteristics in a sample of European residents aged 50 and over. Our initial analysis reveals that in 2013, the proportions of 50+ individuals reporting an inability to afford meat/fish/poultry or fruit/vegetables more than 3 times per week were 11.1% and 12.6%, respectively. It also indicates that not only income but also functional impairment and chronic disease are significantly associated with an increased probability of food insecurity. In a subsequent nonlinear decompositional analysis of the food unaffordability gap between European countries with high versus low FI prevalence, our rich set of covariates explains 36 - 39% of intercountry differences, with household income, being employed, and having functional impairment and/or chronic disease as the most important contributors.
urn:nbn:de:bsz:100-opus-12146
Keywords: D12; D63; I31; 330; food unaffordability; decompositional analysis; older Europeans